New antituberculous drug - Bayona García, Jaime (2009)
Tuberculosis (TB) is a communicable disease that is still a very important health problem in the 21st Century, and it is currently threatening mankind with the emergence of new multidrug resistant (MDR) and extremely resistant (XDR) strains of its causative agent, Mycobacterium tuberculosis. In this scenario, there are very few new antituberculous drugs developed by the pharmaceutical industry, so the therapeutic strategy for this old disease has not undergone substantial changes. Nowadays, every human being is at risk for exposure and for acquiring tuberculosis, so that people acquiring the disease may be exposed to a prolonged therapy schedule, or they may even face death because of lack of effectiveness of antituberculous drugs in MDR or XDR TB cases.